Analysis of Cardiovascular Risk Factors in Patients with Coronary Heart Disease Qualified for Off-Pump Coronary Bypass - Serhii S. Sas; Serhii A. Rudenko (Український журнал серцево-судинної хірургії, 2023)
The aim. To analyze the prevalence of cardiovascular risk factors for circulatory diseases in patients with coronary heart disease (CHD) after coronary bypass surgery (off-pump coronary artery bypass grafting).